Capacity, sustainability, and the community benefits of municipal utility ownership in the United States. Issue 2 (2nd April 2020) - Homsy, George C.
ABSTRACT: Most literature on utility sustainability focuses on internal operations; this misses the role that utilities could play within a community. This study measures the impact of municipal ownership of water and electric utilities on the sustainability policymaking of local governments. I find that municipalities with government-owned water utilities adopt more sustainability measures than those with investor-owned service. Similarly, municipally-owned electric utilities have higher levels of energy sustainability in the community, but not in government operations. The utilities provide fiscal and technical capacity to municipalities. Interdepartmental coordination also strongly predicts sustainability policymaking. This study brings potential community benefits to the discussion of private investment in public service delivery.